1997
DOI: 10.1901/jeab.1997.67-246
|View full text |Cite
|
Sign up to set email alerts
|

Biological Substrates of Operant Conditioning and the Operant—respondent Distinction

Abstract: At the outset I should identify myself as a fellow advocate of the views of Donahoe and his colleagues-as someone who shares their selectionistic approach to behavior, admires their work, and embraces their positions on This research was supported by grants from the National Institute on Drug Abuse (DA-05107 and DA-07747) and the Air Force Office of Scientific Research (89-0213). I thank my colleague James D. Belluzzi for invaluable contributions on a daily basis to all aspects of the experimental and theoreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…As such, it is compatible with various theoretical interpretations. Some have suggested that the fundamental effect of reinforcement is simply to strengthen behavior, possibly irrespective of antecedent events (Kemp, 1997;Stein, 1997); others have suggested that that reinforcement only alters the stimulus control of behavior, where stimuli include all sensory events within and without the skin (Donahoe & Palmer, 1994;Donahoe, Palmer, & Burgos, 1997). According to the latter view, behavior change is possible even if the environment is held constant, because the control exerted by this environment will vary along a gradient of probability according to contingencies of reinforcement, deprivation, and so forth.…”
Section: David C Palmer Smith Collegementioning
confidence: 99%
“…As such, it is compatible with various theoretical interpretations. Some have suggested that the fundamental effect of reinforcement is simply to strengthen behavior, possibly irrespective of antecedent events (Kemp, 1997;Stein, 1997); others have suggested that that reinforcement only alters the stimulus control of behavior, where stimuli include all sensory events within and without the skin (Donahoe & Palmer, 1994;Donahoe, Palmer, & Burgos, 1997). According to the latter view, behavior change is possible even if the environment is held constant, because the control exerted by this environment will vary along a gradient of probability according to contingencies of reinforcement, deprivation, and so forth.…”
Section: David C Palmer Smith Collegementioning
confidence: 99%
“…In a classic example, biobehavioral data have shown that respondent processes in food aversion are enduring and do not require immediate pairing (Garcia, Kimeldorf, & Koelling, 1955). Biological sources of information can inform the discussion as to whether theoretically it is worthwhile to consider conditioning separate or interlocking processes (Stein, 1997). Maintaining the operant-respondent distinction may largely be for the sake of established procedures in applied behavior analysis and for instructional ease when introducing these concepts.…”
Section: Operant Respondingmentioning
confidence: 99%
“…A good example of this is Lubinski and Thompson's (1987, 1993) experimental model for studying private events in which the discriminative function of the effects produced by different substances played an essential part in controlling discriminative behavior of rats. Perhaps closer to neuroscience than behavioral pharmacology, techniques used in cellular and molecular neuroscience are another suitable example, such as in vitro reinforcement (Stein, 1997; Stein, Xue, & Belluzzi, 1993, 1994) and preparations that use simplified neuronal circuits in order to understand the physiological processes related to operant and respondent learning (Baxter & Byrne, 2006; Brembs, Baxter, & Byrne, 2004; Lorenzetti, Mozzachiodi, Baxter, & Byrne, 2006; Mozzachiodi & Byrne, 2010; Mozzachiodi, Lorenzetti, Baxter, & Byrne, 2008). As I will argue, all this results in new neuroscientific findings that can pose new experimental and conceptual questions for behavior analysis (Zilio, 2013).…”
Section: Against Strong Autonomymentioning
confidence: 99%